2023
DOI: 10.1021/acs.bioconjchem.3c00040
|View full text |Cite
|
Sign up to set email alerts
|

AJICAP Second Generation: Improved Chemical Site-Specific Conjugation Technology for Antibody–Drug Conjugate Production

Abstract: The site-directed chemical conjugation of antibodies remains an area of great interest and active efforts within the antibody–drug conjugate (ADC) community. We previously reported a unique site modification using a class of immunoglobulin-G (IgG) Fc-affinity reagents to establish a versatile, streamlined, and site-selective conjugation of native antibodies to enhance the therapeutic index of the resultant ADCs. This methodology, termed “AJICAP”, successfully modified Lys248 of native antibodies to produce sit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 38 publications
1
45
1
Order By: Relevance
“…A previous in vivo efficacy and pharmacokinetic study revealed that the biological profile of Lys248 ADC was like that of Lys288 ADC. 11 However, in the present stability study, the intermediates exhibited a dissimilar behavior. Lys248-related compounds were found to be more stable than Lys288-related compounds.…”
Section: ■ Results and Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…A previous in vivo efficacy and pharmacokinetic study revealed that the biological profile of Lys248 ADC was like that of Lys288 ADC. 11 However, in the present stability study, the intermediates exhibited a dissimilar behavior. Lys248-related compounds were found to be more stable than Lys288-related compounds.…”
Section: ■ Results and Discussioncontrasting
confidence: 51%
“…MC-VC-MMAE (CAS#646502-53-6) was purchased from NJ Biopharmaceuticals, LLC (USA). Peptide reagents (1a and 1b) were prepared according to a published method . All other chemical reagents were purchased from Sigma-Aldrich (USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 To establish a robust and reliable PEGylation using the continuous mode, some challenges still remain. For example, process development including understanding critical process parameters, PEG reagent screening to replace NHS ester having risk of overreactions, 35 detailed conjugation site analysis by peptide mapping, and normal operating range identification was not complete in the present study. Further investigations to establish the ideal continuousmode-mediated PEGylation are currently underway.…”
Section: Special Topic Synthesismentioning
confidence: 89%